Digital Transformation of Pesantren in the VUCA Era: Learning Technological Adaptation from Pesantren - Khusniyah, Khusniyah (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2025)
The digital era, marked by the VUCA phenomenon (Volatility, Uncertainty, Complexity, Ambiguity), demands that Islamic boarding schools (pesantren) formulate adaptive and innovative strategies to remain relevant and produce students (santri) prepared to face contemporary challenges. This study aims to explore the strategies of Pondok Pesantren Darul Fiqhi and Pondok Pesantren Matholi’ul Anwar Lamongan in responding to the VUCA phenomenon and to identify forms of Islamic education transformation in the digital age. This research uses a qualitative case study approach with a multisite design. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that Pondok Pesantren Darul Fiqhi responds to VUCA by developing students' critical thinking skills, equipping them with practical competencies, and maintaining a curriculum grounded in classical Islamic texts (kitab kuning). Meanwhile, Pondok Pesantren Matholi’ul Anwar emphasizes the development of critical thinking, the strengthening of students' practical skills, and the prioritization of character building and the preservation of traditional kitab kuning studies. A key form of digital transformation implemented by both pesantren is the use of YouTube live streaming for kitab kuning learning. This study contributes to the discourse on how pesantren can adapt to the digital era without abandoning traditional Islamic values.